Sao Tome and Principe : Staff Report for the 1999 Article IV Consultation and Request for an Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2000)
In the fiscal area, the primary budget balance of Sao Tome and Principe has turned around from a deficit of 2.2 percent of GDP in 1997 to a surplus of 0.7 percent of GDP in 1998 (Dobra 1.9 billion). The primary surplus is estimated to have increased further to 1.3 percent of GDP in 1999. Monetary policy has remained tight in 1999, as the central bank has maintained the reserve requirement ratio at 22 percent and commercial banks have kept their savings and lending rates substantially above the central bank reference interest rate.